Gabon and the new partnership for Africa's development (NPAD) - (:unkn) unknown (My University, 2008)
After the Cold War, globalization has become one of the major contemporary economic and political transformations. These changes led to the reconfiguration of the world map and the international relations. From this point of view, regionalism seemed to be one of the answers to the benefits of these economic changes at a global level and to the historical example without common measurement of NEPAD. That is to say that the co-operation between States is dominated henceforth by the dynamics of partnership. Today, the partnership for the development has become, politically speaking, one of the major topics in the international relations in the era of the new regionalism. It is about an international event which, on the theoretical level renews and enriches the international analysis by combining transnational flows and the formation of institutions and, on the practical level, diffuses a whole vision of the world while redefining the whole concept of world power. With regard to the institutionalization of NEPAD, the African continent tries to find new ways of keeping up with globalization in order to change its internationally marginal position to avoid its “confinement to the periphery of world politics”. Therefore, NEPAD is at the same time a political answer to the international fact of regionalization and an alternative to the suffering of the institutions, or rather a means of reacting to the lack the impossibility of implementing sustainable democratic values on this continent. This justifies this slippage of the legitimacy of power, resulting from the “African peer review mechanism”. The involvement of Gabon in this transnational dynamics is, above all, due to the external inspection from money-lenders. It is, thus, a question for this country of transforming an external constraint of inspection into a domestic political strategy in order to abide by the rule of international and regional system. While endeavouring to ap
Keywords: African Research